Retroperitoneal liposarcoma: case of a giant tumour inside the abdomen - Khan, Shahzaib; Areeb Zafar,; Murk Lakhani,; Arsalan Baig,; Ali Hassan,; Owais Khan, (Journal of the Pakistan Medical Association, 2023)
Retroperitoneal liposarcomas are rare malignant tumours that often grow rapidly in size and become symptomatic late in the disease course, posing diagnostic and therapeutic challenges. Although abdominal imaging can reliably diagnose the tumour, definitive diagnosis is only possible through biopsy after surgical excision, which remains the primary treatment modality for these tumours. Long-term survival is primarily determined through histologic grade and post-resection tumour margins. We report the case of a 43-year-old male patient, seen at Dr Ruth KM Pfau Hospital Karachi, who underwent successful surgical excision for a well-differentiated retroperitoneal liposarcoma and had no radiographic evidence of local recurrence at both 3 and 12-month follow-ups. Keywords: Retroperitoneal liposarcoma, surgical excision, tumour recurrence, tumour grade.